Les rivages des Bermudes et les formes littorales de dissolution du calcaire - Taillefer, François (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
The littoral morphology of the Bermudas is an erosional morphology in limestones, the main processes being mechanical action and solution. The temperatures, in January and February, of the waters washing the Bermudas, are low enough to prevent the growing of true coral reefs. Therefore, it is not the morphology of a coral reef.The predominance of wave-cut cliffs is the most striking feature, despite the low and gently rolling topography. There are, however, other types of coasts on the islands, the mangrove being found on many sheltered shores. The writer thus opposes the sheltered shores of the sounds to the ones exposed on the southcoast, while the shores of the north and north-east coasts belong to an intermediate type.The steplike arrangement of the coastal forms of solution of the Bermudas limestones is primarily linked to the amount of the tidal range. These features are similar to those described on the shores of the warm seas, where the tide is negligible or weak.The Bermudas occupy an intermediate position between the regions where reefs are built by corals, and those, to the north, where solution, helped by other processes, occurs without compensation.